Probiotic, zinc and lactose-free formula in children with rotavirus diarrhea: Are they effective? - (:unkn) unknown (WILEY-BLACKWELL, 2011)
Background: The aim of the present study was to evaluate the effectiveness of zinc, probiotic bacteria, and lactose-free formula and their different combinations in the treatment of rotavirus diarrhea in young children. Methods: Eight different treatment groups were formed: group 1, 60 patients receiving Saccharomyces boulardii; group 2, 60 patients receiving zinc; group 3, 60 patients receiving lactose-free formula; group 4, 60 patients receiving S. boulardii plus zinc; group 5, 60 patients receiving S. boulardii plus lactose-free formula; group 6, 60 patients receiving zinc plus lactose-free formula; group 7, 60 patients receiving S. boulardii plus zinc plus lactose-free formula; group 8, 60 patients receiving only oral and/or parenteral rehydration solutions. Results: No statistically significant differences were found in the time to resolution of fever after intervention between the treatment groups and the control group. The time to resolution of vomiting was significantly lower in group 4 compared with groups 1 and 5. The duration of diarrhea was significantly reduced in groups 2 and 4 compared to control. Astatistically significant difference in the duration of hospitalization was observed for the groups 2 and 4 in comparison to the control group. Conclusions: Adifferent combination of adjunct therapies did not seem to bring additional value to rehydration therapy in children with rotavirus diarrhea except for in those receiving only zinc and zinc plus S. boulardii. Further studies are required to determine the optimal protocol of adjunct therapy use in children with rotavirus diarrhea.
Keywords: children; lactose-free formula; probiotic; rotavirus; zinc; RANDOMIZED CONTROLLED-TRIAL; ACUTE INFECTIOUS DIARRHEA; YOUNG-CHILDREN; ACUTE GASTROENTERITIS; DOUBLE-BLIND; LACTOBACILLUS GG; MANAGEMENT; INFANTS; PREVENTION; SUPPLEMENTATION